Menerima Instagram Apa Adanya: Melacak Pemaknaan dan Fantasi Individu Pelaku Aktivitas Kerja Sebagai Admin terhadap Aplikasi Media Sosial Instagram - Hanz Sinelir (Sanata Dharma University, 2022)
After the birth of the internet, the relationship between humans and technology is often discussed academically in two poles, namely utopia and dystopia. This study uses examples from the popular social network platform Instagram to find out how users interpret their relationship with technology. The subjects in the study were Instagram account admins, either from commercial brands or social movements. The job of an